'Seeing' my Beloved. (9th November 2018) - Takhar, Opinderjit Kaur
Abstract : The discussion in this chapter focuses on the concept of dar?an from a Sikh perspective by analysing teachings from the Guru Granth Sahib on the subject of 'seeing' the Divine. Sikhi (Sikh teachings) emphasises the Ultimate Divine as formless and experienced through the senses. Indeed, Sikhi refers to this experience as blissful union with one's Beloved. This chapter explores Sahaj, mystical union with the Divine, through an analysis of teachings around dar?an in Sikh teachings. Time and time again, the teachings of the Guru Granth Sahib allude to the bestowing of Nadar as the opportunity to transcend one's consciousness from being manmukh (worldly/self-orientated) to gurmukh (attuned to the Divine). To become gurmukh is the concept of an awakened mind; according to Sikhi, a gurmukh is one who has 'seen' the formless Divine, one who has 'heard' the anahad sabad (the unstruck melody), which suggests a heightening of the senses, an awakening of the man/buddhi.